Social action model with program of cultivation of crab is one of the problem solving altematives of conflict among branchish waterpond society with govemment (Ministry of Forestry of Republic of Indonesia ·Perhutani"). There are different interest among them that the coastal (mangrove forest) in order to a conservation and another side to living of the branch ish waterpond community. The objectives of the research were (1) to describe of the social action components in the study location, and ( - Anna Fatchiya (Buletin Ekonomi Perikanan, 2008)
Social action model with program of cultivation of crab is one of the problem solving altematives of conflict among branchish waterpond society with govemment (Ministry of Forestry of Republic of Indonesia ·Perhutani"). There are different interest among them that the coastal (mangrove forest) in order to a conservation and another side to living of the branch ish waterpond community. The objectives of the research were (1) to describe of the social action components in the study location, and (2) to design a social action model with program of cultivation oferab. The research showed that (1) social action components indicated as (1) the actor components were branchish waterpond and "Perhutani", (b) situational and problem component was a conflict of different interest among coastal pond communitiy with "Perhutani", (c) the objective component mangrove was in order to living for the branch ish waterpond, but for "Perhutani" it was in order to conservation thing, (d) the value and norm component (e) there are legal formal and tradition (informal) about coastal management were adopted by them, and the way of the objective component by branch ish waterpond the mangrove in order to cultivate of fish, settlement, and firewood, and by Perhutani was monitoring and controlling of this (2) the principles of social action were participation, empowering, autonomy, and sustainability. To design of social action model systematically with step by step way. Firstly, planning (data collecting, data analyzing, problem identification, priority problem ellection, decide objective of program), input identlcation, decide of output, decide of outcomes, and evaluation